الأمن النفسي وعلاقته بالأداء الوظيفي لدى عينة من عمال مؤسسة سونلغاز دراسة ميدلنية بالأغواط - بلقيدوم شيماء; بن يطو ماحي; عمومن رمضان (My University, 2023)
The current study aimed to reveal the relationship between psychological security and job performance among the workers of the Sonelgaz Foundation in Laghouat, by knowing the level of psychological security and identifying its most important indicators, and the level of job performance in the study sample, by relying on the descriptive approach and applying two questionnaires to collect data on the variables of the study and distribute them to a sample It was estimated by 56 workers in the Sonelgaz Corporation in a crosssectional way, and after statistical processing of the data, the following results were reached: - The level of psychological security among the workers of the Sonelgaz Corporation in Laghouat is high - The most important indicators of psychological security among the workers of the Sonelgaz Corporation in Laghouat is self-satisfaction. - The level of job performance among the workers of the Sonelgaz Corporation in Laghouat is high - There is a statistically significant relationship between psychological security and job performance among the workers of Sonelgaz Corporation in Laghouat. Keywords: psychological security, job performance